영업/마케팅부문의 6시그마 성공 요인에 관한 연구 - 국내 S전자를 중심으로 - - 권재진 (The Graduate School, Ajou University, 2005)
Nowadays many Korean companies are introducing and adopting Six Sigma to their management strategies or innovation tools to maximize their profit through customer satisfaction. However most companies confront many difficulties and show unsatisfactory results in the sector of sales & marketing. This study has been attempted to find critical success factors of Six Sigma for sales & marketing activities. To achieve the aim of this study, a document study and interviews were performed. The collected questionnaires were processed statistically through data coding and multiple regression analysis, correlation analysis and several descriptive statistics were conducted. The results of this study show that the driving force and participation level of top management, the degree of overall interest of project champions, the level of project reviews of project champions, compensation and incentives for project completion, the level of difficulty using Six Sigma tools and execution ability of project leaders are core factors that influence sales & marketing performance.
학위논문(석사)--아주대학교 경영대학원 :MBA일반경영,2005